1997
DOI: 10.1038/sj.bjp.0701114
|View full text |Cite
|
Sign up to set email alerts
|

The effect of okadaic acid on non‐adrenergic non‐cholinergic contraction in guinea‐pig isolated bronchus

Abstract: 1 We have investigated the role of phosphatases in modulating contractile responses to electrical ®eld stimulation (EFS), methacholine, substance P and capsaicin in guinea-pig isolated main bronchus by use of the phosphatase 1 and 2A inhibitor okadaic acid. 2 Non-adrenergic non-cholinergic (eNANC) contractile responses were elicited by EFS (3 Hz, 20 s, 0.5 ms max. voltage) in the guinea-pig isolated main bronchus in the presence of the non-selective muscarinic antagonist, atropine (1 mM), the non-selective b-a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
6
0

Year Published

1998
1998
2015
2015

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 40 publications
2
6
0
Order By: Relevance
“…Previous studies have shown that okadaic acid facilitated neuropeptide release (Hingtgen & Vasko, 1994), but had no eect on calcium entry (Cholewinski et al, 1993) or desensitization (Docherty et al, 1996) induced by capsaicin in rat DRG neurones. The latter ®ndings are consistent with a lack of eect of okadaic acid on capsaicininduced contractile responses in the guinea-pig (Harrison et al, 1997).…”
Section: Discussionsupporting
confidence: 84%
See 2 more Smart Citations
“…Previous studies have shown that okadaic acid facilitated neuropeptide release (Hingtgen & Vasko, 1994), but had no eect on calcium entry (Cholewinski et al, 1993) or desensitization (Docherty et al, 1996) induced by capsaicin in rat DRG neurones. The latter ®ndings are consistent with a lack of eect of okadaic acid on capsaicininduced contractile responses in the guinea-pig (Harrison et al, 1997).…”
Section: Discussionsupporting
confidence: 84%
“…We have previously reported that the protein phosphatase 1 and 2A inhibitor, okadaic acid, inhibited the contractile response following stimulation of eNANC nerves but not to capsaicin in guinea‐pig isolated bronchus (Harrison et al , 1997). This suggested that protein phosphorylation/depho‐sphorylation regulates neuropeptide release from airway sensory nerves following activation of voltage‐dependent calcium channels.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Guinea‐pig isolated bronchus is a useful biological readout of neuropeptide release from airway sensory nerves and we have shown that various pharmacological agents including the phosphodiesterase (PDE)4 inhibitor, Ro‐201724 ( Spina et al ., 1995 ); the phosphatase 1/2A inhibitor, okadaic acid ( Harrison et al ., 1997 ) and the ORL 1 ‐receptor agonist, nociceptin ( Shah et al ., 1998 ) attenuated the eNANC response in this preparation. We have therefore investigated whether anandamide stimulates vanilloid receptors on airway sensory nerves and the role of cannabinoid receptors in modulating the eNANC response in guinea‐pig airways.…”
Section: Introductionmentioning
confidence: 99%
“…Ref. (33)). This exceptional case might elucidate the inhibitory mechanism by comparing CCh-contraction with that with ionomycin in the BCM.…”
Section: Discussionmentioning
confidence: 99%